Public Expenditure and Financial Accountability Assessment of West Pokot County, Kenya - World Bank (World Bank, Washington, DC, 2020)
The rationale for the public expenditure and financial accountability (PEFA) assessment is to provide a clear and deeper understanding about the functioning of public financial management (PFM) systems as well as the organizational aspects of existing institutions at county levels. The results of the analysis provide useful insights into relevant entry points for desired PFM-related reforms and a benchmark for the necessary upgrade of the PFM systems which are still in the early stages of development within Kenya’s devolved units of government. This assessment was organized and commissioned by Kenya Institute for Public Policy Research and Analysis (KIPPRA) in collaboration with the World Bank and involves other organizations. KIPPRA also carried out the actual survey and assessment and was responsible for management and monitoring of the exercise. The assessment period covers three financial years, namely FY2013-14, FY2014-15, and FY2015-16, and focused on various indicators and dimensions as defined in the PEFA assessment tools.